A Removable Insertion Shuttle for Ultraflexible Neural Probe Implantation with Stable Chronic Brain Electrophysiological Recording. Issue 6 (29th January 2020) - Zhang, Shun; Wang, Chengjun; Gao, Huan; Yu, Chaonan; Yan, Qinghao; Lu, Yuchen; Tao, Zhehao; Linghu, Changhong; Chen, Zhou; Xu, Kedi; Song, Jizhou
Abstract: Ultraflexible neural probe is an ideal tool for brain research, which can reduce the mechanical interfacial mismatch between electrodes and brain tissue and can thus reduce the tissue's inflammation and extend the electrodes' service life. However, the low stiffness of ultraflexible neural probe makes it susceptible to bending and buckling during insertion into brain. Here, a simple yet robust design of removable insertion shuttle consisting of a steel needle with a dissolvable spheroid micropost is reported for ultraflexible neural probe implantation. The dissolvable spheroid micropost of insertion shuttle is fabricated by the simple dip‐coating process based on the competition and balance between the surface tension and gravity. A temporary engaging mechanism enabled by the micropost engaged into the via hole on the tip of ultraflexible neural probe is adopted to enable an easy and quick implantation. Experimental studies reveal the fundamental aspects of the design of removable insertion shuttle and the operation of implantation. In vivo implantation of ultraflexible neural probes into rat's brain illustrates the unusual capabilities of removable insertion shuttle with the accurate positioning of probe at desired depth and the stable chronic brain electrophysiological recording, which show great potential in both basic neuroscience and clinical applications. Abstract : A simple yet robust removable insertion shuttle by dip coating is used to assist the implantation of ultraflexible neural probe into brain. In vitro and in vivo experiments illustrate the unusual capabilities of removable insertion shuttle with the accurate positioning of probe at desired depth and the stable chronic brain electrophysiological recording.